Prosperity of the Process and Issuance of Regional Bonds and Risk of Public Bonds Registration in Indonesia - Sarah Wina Annisa; Mega Rahmawati Combo; Azizah Afaf (Fakultas Hukum Universitas Airlangga, 2019)
AbstractMaking transactions can get a lot of profit, then there are several ways, one of which is in the form of investing. To make investments can be done by individuals or a person entity that has excess funds or is often called a company securities. Regulations regarding risk in Municipal Bonds are not the same as arrangements in corporate bonds and corporate bonds themselves, basically payment of Municipal Bonds made by this Regional Government comes from funds from the utilization / use of infrastructure built from publishing the regional bonds and reserve funds in the APBD must be allocated to repayment. it is important to research how to regulate and the process of issuing regional bonds. From this background can be drawn formulation of the problem, namely, How to Analyze the regulation and issuance process of Bonds Regions in Indonesia?The results of the formulation of the problem that the author took was that all the rulesrelated to procedures and issuance of municipal bonds is clear and regulated in law -invite, namely Law Number 33 of 2004 concerning Financial Balance between the Central Government and Regional Government, Government Regulation Number 30 In 2011 concerning Regional Loans, Minister of Finance Regulation Number 180 / PMK.07 / 2015 concerning Amendments to Regulation of the Minister of Finance Number 111 / PMK.07 / 2012 concerning Procedures for Issuance and Accountability of Bonds Area. Issuance of bonds can also be done through a public offering.